2006
DOI: 10.1158/1535-7163.mct-06-0315
|View full text |Cite
|
Sign up to set email alerts
|

A urokinase-activated recombinant anthrax toxin is selectively cytotoxic to many human tumor cell types

Abstract: Urokinase plasminogen activator (uPA) is a tumor-specific protease highly expressed in several types of solid tumors and rarely present on normal cells under physiologic conditions. Due to its high expression on metastatic tumors, several different strategies have been used to target the urokinase system. These have mostly led to tumor growth inhibition rather than tumor regression. A different approach was adopted by replacing the furin activation site on a recombinant anthrax toxin with a urokinase activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 27 publications
(22 reference statements)
1
48
0
Order By: Relevance
“…Diverse cell lines treated with LF-PA show a wide range of sensitivities to the toxin (9,(20)(21)(22)(23)(24)(25), and cell death occurs only in cells that have impaired MAPK kinase function (21). We hypothesized that such phenotypic differences might enable microarray-based identification of other genes whose differentially elevated or reduced expression correlates with differential toxin lethality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse cell lines treated with LF-PA show a wide range of sensitivities to the toxin (9,(20)(21)(22)(23)(24)(25), and cell death occurs only in cells that have impaired MAPK kinase function (21). We hypothesized that such phenotypic differences might enable microarray-based identification of other genes whose differentially elevated or reduced expression correlates with differential toxin lethality.…”
Section: Resultsmentioning
confidence: 99%
“…GABRIEL software (26) separated cancer cell lines (SK-MEL-5, SK-MEL28, M-14, MALME-3M, MDA-MB-435, MDA-N, SK-MEL-2, HL-60, MCF7, SW-620, EKVX, and A549) into two groups, LF-PA-sensitive and LF-PA-resistant, based on previous reports (9,(20)(21)(22)(23)(24)(25). GABRIEL (27) was used for correlation of steady-state levels of expression with toxin lethality.…”
Section: Methodsmentioning
confidence: 99%
“…Different types of cytolytic toxins, such as anthrax toxin, aerolysin, two-chain ·-hemolysin, and hecate have been used in fusion proteins or conjugates to either directly target the tumor cell surface through ligands and receptors, or be activated through tumor-specific proteases, such as urokinase, PSA, cathepsin B and MMPs (16)(17)(18)(19). In a previous study, we have shown that an MMP2 cleavable melittin, the poreforming toxin from honey bee, conjugated with avidin can specifically target tumor cells in vitro and in vivo (20).…”
Section: Introductionmentioning
confidence: 99%
“…Duration and severity of inflammation increases the risk of Colorectal cancer (CRC) development by about 60% in IBD patients [5]. Chronic inflammation represents the appropriate microenvironment for tumor development via stimulation of immune cells [6].…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%